Using student voice to develop student leadership in an inner city school - Weir, Dwight (2014)
The lack of pupil voice activities within my work context influenced the introduction of a variety of opportunities for pupils to contribute to the leadership of their year group. In order for pupils to effectively lead, it was necessary to develop within them leadership skills. With the intention of promoting pupil voice, more specifically consultation and engagement (the lack identified by pupils), were used as the main tool to develop the content and delivery of the leadership development programme. This study assesses the extent to which consultation and engagement could be used to aid student leadership development in an inner city secondary school.